THE MEANING OF SITOU TIMOU TUMOU TOU AS A MODEL OF WOMEN EMPOWERMENT MANAGEMENT IN MAPALUS HOUSE IN SOUTHEAST MINAHASA, NORTH SULAWESI - Imran, Treesje; Mambu, Laurens; Lapalelo, Beatrix; Baali, Yongker; Kojongian, Patricia Jeaneth Cyntia (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
Si Tou Timou Tumou Tou is a philosophy of the Minahasa people, meaning that humans live to humanize others. The term